Influence of back‐to‐back VSC‐HVDC project on the operation characteristics of Hubei power grid. Issue 13 (4th December 2017) - Cai, Defu; Zhou, Kunpeng; Wang, Wenna; Liu, Haiguang; Cao, Kan; Wang, Ying
Abstract : The synchronous interconnection between Chongqing and Hubei power grid is planned to be unsynchronised by back‐to‐back voltage source converter based high‐voltage direct current (VSC‐HVDC) project, which has great impact on the operation characteristics of Hubei power grid. In this study, the basic information of back‐to‐back VSC‐HVDC project was introduced. The influence of this project on the operation characteristics of Hubei power grid was analysed in detail, including power flow, short‐circuit current, transient stability and frequency characteristic. The corresponding grid reinforcement measures were proposed to solve power flow over‐limit and transient instability problems caused by this project. The study has some reference value for the planning and operation of Hubei power grid and the design of other similar HVDC transmission projects.